(untitled) (LEGAL DIALOGICA, 2025)
This study aims to analyze the Linkage and Application of the Rahn Tasjily Agreement in PT. Sharia pawnshops according to the rule of law. The research method used in writing this thesis is a normative method, which will be based on secondary literature or data, with the coverage of primary, secondary and tertiary legal materials. The implementation of the Rahn Tasjily contract on Amanah products at PT Pegadaian Syariah is in principle in accordance with sharia provisions, especially the DSN-MUI Fatwa No. 68/2008 which allows the submission of proof of ownership (BPKB) for movable objects as collateral, while the goods are still used by the customer. However, in practice, irregularities are still found, especially in the incorporation of the cost of maintaining the guarantee (mu’nah) into the principal debt which causes inconsistency with the fatwa and gives rise to the element of gharar. In addition, the use of fiduciary guarantees and immovable objects such as land in the Rahn Tasjily contract creates a legal conflict with the provisions of national law, and shows that sharia principles have not been implemented in a kaffah manner in the product. PT Pegadaian Syariah should improve the contract structure by clearly separating maintenance costs from the principal debt to maintain transparency and avoid gharar, as well as stop the practice of using fiduciary guarantees in sharia contracts to maintain the purity of the Rahn Tasjily principle. In addition, the government and related authorities need to formulate special regulations in the form of the Sharia Guarantee Law so that sharia-based contracts such as Rahn have legal force equivalent to conventional guarantees, and Pegadaian also needs to ensure that the object of collateral is limited to movable objects in accordance with applicable civil law. Abstrak: Penelitian ini bertujuan untuk menganalisis Keterkaitan dan Penerapan Akad Rahn Tasjily Dalam Produk Amanah PT. Pegadaian Syariah Menurut Aturan Hukum. Metode Penelitian yang digunakan dalam penulisan skripsi ini adalah metode normatif yaitu akan bertitik tolak pada bahan pustaka atau data sekunder, dengan cakupan bahan hukum primer, sekunder dan tersier. Pelaksanaan akad Rahn Tasjily pada produk Amanah di PT Pegadaian Syariah secara prinsip telah sesuai dengan ketentuan syariah, khususnya Fatwa DSN-MUI No. 68/2008 yang membolehkan penyerahan bukti kepemilikan (BPKB) atas benda bergerak sebagai jaminan, sementara barang tetap digunakan oleh nasabah. Namun, dalam praktiknya masih ditemukan penyimpangan, terutama dalam penggabungan biaya pemeliharaan jaminan (mu’nah) ke dalam pokok utang yang menyebabkan ketidaksesuaian dengan fatwa dan menimbulkan unsur gharar. Penggunaan jaminan fidusia dan objek tidak bergerak seperti tanah dalam akad Rahn Tasjily menimbulkan konflik hukum dengan ketentuan hukum nasional, serta menunjukkan belum terlaksananya prinsip syariah secara kaffah dalam produk tersebut. PT Pegadaian Syariah sebaiknya memperbaiki struktur akad dengan memisahkan secara jelas biaya pemeliharaan dari pokok utang guna menjaga transparansi dan menghindari gharar, serta menghentikan praktik penggunaan jaminan fidusia dalam akad syariah untuk menjaga kemurnian prinsip Rahn Tasjily. Selain itu, pemerintah bersama otoritas terkait perlu merumuskan regulasi khusus dalam bentuk Undang-Undang Jaminan Syariah agar akad-akad berbasis syariah seperti Rahn memiliki kekuatan hukum yang setara dengan jaminan konvensional. Kata Kunci: Hukum, Rahn Tasjily, Pegadaian,